John and Elaine Steinbeck on part of an European Tour - Jacques Guittet:::Creator::::::::::::
John and Elaine Steinbeck at a gathering aboard the dock of the MV Saturnia, part of Societe di Navigazione Italia cruise line. John stands amid the crowd looking upward. Original in safe